Integrating green infrastructure distribution and green corridor mapping with proposed green trail area and wildlife-human conflict using remote sensing-GIS approach - Syarifuddin, Misbari; Anak Gisen, Jacqueline Isabella; Nur Arissa Farhanis, Mohd Rosli); Amir Asyraf, Mohd Fauzi; Aishah, Abu Bakar (Universiti Putra Malaysia, 2024)
Most people now prefer to live in cities, and the urban population has grown significantly. The decrement of urban green corridors causes an essential need for livability in highly populated areas. The needs of population health and sustainable city development are put under prolonged stress by the shortage of publicly accessible green infrastructure and its placement in inappropriate areas. The inventory of green corridor areas and the distribution of significant infrastructure are not fully understood, thus encouraging conflicts between residents and wildlife and increasing flood risk in their vicinity. Optical satellite images were required to (1) develop a green corridor (GC) map, (2) investigate the green infrastructure (GI) demand with the existing land use, and (3) propose new green trails (GT) in the Kuantan district using a geospatial approach. NDVI and site suitability analysis were carried out on Landsat OLI and Sentinel-2 MSI images, which were integrated with GIS tools to achieve all the objectives. A GC map has been developed, and five new proposed areas for GI development have been identified. Based on the results, 5 proposed green trails (3 long GTs, 2 short GTs) with a total length of 79.3 km are scattered in the Kuantan district at the most suitable site, identified using a geospatial approach. This study supports SDG 15: Life on Land, where green corridors reinforce biological connectivity, provide conducive space for high-populated areas, and minimize the negative impact of urbanization on the designed areas of GC, GI and GT in the developing city of Kuantan.